INTRODUCTION - Mechanism-based Development of Natural Products for Human Health - Basil D Roufogalis; Arthur D Conigrave; Emanuel E Strehler (Frontiers Media S.A., 2013)
This Special Issue of the Journal of Pharmacy and Pharmaceutical Sciences arises from an inaugural conference on "Mechanism-Based Natural Product Development" held at Whistler Mountain, Canada on September 21-22, 2012. The aim of the conference was to bring together scientists from various disciplines to discuss the development of new therapeutic products from natural medicines based on mechanistic and related scientific studies. It provided an opportunity to explore new directions in natural medicine research and development, with the ultimate objective of leading to greater integration of natural and conventional synthetic pharmaceutical medicines for the health of the community worldwide. The concept for this conference and the Special Issue has come from the growing interest internationally in traditional and natural medicinal health products in recent years. It may, at first, appear surprising that developed countries are re-embracing natural product research and development. There are of course many reasons for this, including growing community interest in natural products providing improved health and wellbeing, the growing difficulty and cost of maintaining a pipeline of effective and, above all, safe new products for chronic diseases in the mainstream pharmaceutical industry, and the knowledge that many of our small drug pharmaceutical medicines have come from plants and other organisms. But as traditional natural product medicines increasingly enter the mainstream, the call for evidence to support their use also grows louder. Essential to the acceptance of natural medicines are the validation of their traditional uses and identification, isolation and structural characterization of their active components, together with the elucidation of their mechanisms of biological action, adverse effects, and identification of their molecular targets. These requirements provide the focus of this Special Issue. Scientific investigation and development of new health products requires the joining together of many disciplines, including chemistry, pharmacology, pharmacognosy and cell and molecular biology, as well as integration with clinical medicine. Natural product medicines are expected to be multi-component and multi-targeted. Are they effective, safe and properly standardized in their existing formulations? Are there opportunities to isolate single active components for standardization and conventional drug discovery and development? Answering these questions requires collaboration between scientific disciplines focused on a common goal. In line with the aims of the conference, the Special Issue has incorporated review and original research articles related to mechanisms of action in a number of therapeutic areas, mostly from invited speakers at the Whistler conference. Other articles were unsolicited submissions to the Journal that satisfy the scope of the issue. Articles range from reports on efforts to work with traditional owners in the appropriate cultural context, to develop new therapeutics based on traditional literature, to discover new medicinal products, to develop new pharmaceuticals based on the isolation of active chemical components, to develop new methods of delivery, and to identify mechanisms of action. The medical 'territory' includes cancer, heart disease, diabetes and related chronic inflammatory diseases, pain pathways, deafness and infertility. Other articles investigate the quality and safety of products by the application of current analytical methods, the potential for interactions of natural products (e.g., cranberry) with pharmaceutical medicines and the variability of a selection of similar natural product medicines with regard to their contents of therapeutically beneficial and marker compounds, as claimed on the product labels. In addition, the issue includes the abstracts of posters that formed an important part of the conference, especially from postgraduate students and postdoctoral fellows. These are included as Proceedings. We are indebted to the scientists who willingly gave their time and resources to attend the Whistler conference and, in many cases, submitted manuscripts for inclusion in this Special Issue. The delegates and contributors came from many places, near and far, to make this inaugural conference on mechanism-based natural product development a success. Such a conference and the subsequent proceedings in the Special issue are not possible without the work of many. We thank the organizing and scientific committee for their support and valuable suggestions. A conference of this scope would not be possible without sponsorship; this includes especially the National Health Products Research Society of Canada, the Canadian Society for Pharmaceutical Sciences and several Universities. Major support, without program or editorial input, was provided by SOHO Flordis International (SFI). We commend them for believing in the quest for clinically proven and research-based products based on an understanding of underlying mechanisms. The support of Purapharm International is also gratefully acknowledged. We would like to dedicate this Special Issue to Professor Allan SY Lau of the University of Hong Kong, who contributed enthusiastically to the organization of the conference and its program, but was ultimately unable to attend due to his untimely passing. Professor Lau was a pioneer in the integration of natural and orthodox medical studies and his inspiration will be greatly missed. Basil D Roufogalis, Arthur D Conigrave and Emanuel E Strehler Co-Guest Editors